2015
DOI: 10.1111/bjd.13440
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous panniculitis-like T-cell lymphoma in children: a detailed clinicopathological description of 11 multifocal cases with a high frequency of haemophagocytic syndrome

Abstract: Subcutaneous panniculitis-like T-cell lymphoma in children -a detailed clinico-pathological description of 11 multifocal cases: high frequence of hemophagocytic syndrom

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 10 publications
2
25
1
2
Order By: Relevance
“…Cytotoxic T cell lymphomas or lymphoproliferation within the skin and subcutaneous tissues are divided in two different entities in the present 2008 WHO classification; SP TCL, restricted to cases with αβ-phenotype and primary cutaneous gamma-delta T cell lymphoma (PCGD-TCL) with γδ-phenotype. Patients with SP TCL had the best outcome in our series, with a pOS at 5 years of 0.78, and this is in accordance to earlier reports [13,14]. Only one patient in our series was diagnosed with PCGD TCL, and that patient died from disease, in accordance to what is known from the literature [15].…”
Section: Discussionsupporting
confidence: 92%
“…Cytotoxic T cell lymphomas or lymphoproliferation within the skin and subcutaneous tissues are divided in two different entities in the present 2008 WHO classification; SP TCL, restricted to cases with αβ-phenotype and primary cutaneous gamma-delta T cell lymphoma (PCGD-TCL) with γδ-phenotype. Patients with SP TCL had the best outcome in our series, with a pOS at 5 years of 0.78, and this is in accordance to earlier reports [13,14]. Only one patient in our series was diagnosed with PCGD TCL, and that patient died from disease, in accordance to what is known from the literature [15].…”
Section: Discussionsupporting
confidence: 92%
“…CNS involvement was not detected in any of them. The more detailed clinical and histopathological features of these five patients with this extremely rare skin/subcutis‐restricted lymphoma are described in a series of 11 paediatric patients in a separate report (Oschlies et al , in press). The five patients are alive in CR1 with a median follow‐up of 2·2 years.…”
Section: Resultsmentioning
confidence: 99%
“…[13] The presence of MAS or hemophagocytosis (HPS) might change the management approach and outcome in SPTCL. [14] One study reported 5-year overall survival rates of 91% and 46% in SPTCL patients without and with an HPS, respectively. [1] In SPTCL without associated HPS, careful observation, systemic steroids or other immunosuppressive agents could be considered first, whereas in cases of solitary or localized skin lesions, radiotherapy with electrons is advised.…”
Section: Discussionmentioning
confidence: 99%